A teoria junguiana dos tipos psicológicos - Baptista, Marcia Loureiro (2006)
This study seeks to explore the use of Carl Gustav Jung s theory of psychological types as an important diagnostical tool, providing guidelines to child treatment as well as to the orientation of the child s family and the professionals envolved. Researches already conducted into the adult world have come to corroborate the relevance of the use of both the four functions and the two attitudes described by Jung s theory for a better understanding of people s lives and conducts. This work aims at evaluating the importance of Jung s four functions and two attitudes in the process of forming and structuring the conscience throughout the first childhood, using Junguian typology as a means to understand the psychological dynamics of the child in general. The results of our research reveal that these psychological attitudes and functions play a fundamental role in the development of the child s ego and that Junguian typology is a system that allows for the understanding of the clinic data related to the early years of human life as well as for an accurate psychodiagnosis of the child patient; moreover, it may work as a tool for the understanding of family dynamics, propitiating communication and respect towards each member s individuality